Comparative virus replication and host innate responses in human cells infected with three prevalent clades (2.3.4, 2.3.2, and 7) of highly pathogenic avian influenza H5N1 viruses - Sun, H.; Sun, Y.; Pu, J.; Zhang, Y.; Zhu, Q.; Li, J.; Gu, J.; Chang, K.-C.; Liu, J. (American Society for Microbiology, 2014)
Highly pathogenic avian influenza H5N1 virus clades 2.3.4, 2.3.2, and 7 are the dominant cocirculating H5N1 viruses in poultry in China. However, humans appear to be clinically susceptible mostly to the 2.3.4 virus clade. Here, we demonstrated that A549 cells and human macrophages infected with clade 2.3.4 viruses produced significantly more viruses than those infected with the other two clades. Likewise, clade 2.3.4-infected macrophages caused the most severe cellular damage and strongest proinflammatory response.